Anotasi 200 buku Islam karya Muslim Indonesia - DIAN/INTERFIDEI (Organization) ([Yogyakarta] : Interfidei, 1998)
Annotated works on Islam by Indonesian Muslim writers in the collection of Perpustakaan Institut DIAN/Interfidei.
Includes bibliographical references (p. xxii).
Keywords: Islamic literature -- Indonesia